2004
DOI: 10.1007/s00277-004-0964-6
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of relapsed thrombotic thrombocytopenic purpura

Abstract: Several reports have defined nonfamilial thrombotic thrombocytopenic purpura (TTP) as an autoimmune disorder caused by antibodies to von Willebrand's factor-cleaving protease (vWF-CP). This raises the possibility that rituximab, a monoclonal antibody against CD20 present in B-lymphoid cells, may have utility in the treatment of TTP. We report five consecutively treated patients with relapsed TTP who responded rapidly to immune suppression by rituximab at our institution. These two male and three female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 24 publications
2
49
0
1
Order By: Relevance
“…Furthermore, in some cases, rituximab is effective in patients with TTP with normal ADAMTS13 activity (Reddy et al, 2005;Kameda et al, 2007). These data suggest that rituximab cannot simply be decreasing levels of ADAMTS13 autoantibody production by depleting B cells, but must be functioning by at least one other mechanism.…”
Section: Use Of Rituximab In Ttpmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, in some cases, rituximab is effective in patients with TTP with normal ADAMTS13 activity (Reddy et al, 2005;Kameda et al, 2007). These data suggest that rituximab cannot simply be decreasing levels of ADAMTS13 autoantibody production by depleting B cells, but must be functioning by at least one other mechanism.…”
Section: Use Of Rituximab In Ttpmentioning
confidence: 87%
“…Furthermore, in patients who initially responded to rituximab treatment but then relapsed, re-treatment with rituximab appeared effective, with durable responses induced again (Ahmad et al, 2004;Fakhouri et al, 2005;Galbusera et al, 2005;Reddy et al, 2005;Herbei & Venugopal, 2006;Heidel et al, 2007;Patino & Sarode, 2007). Herbei and Venugopal (2006) have suggested that rituximab maintenance may be beneficial for some patients.…”
Section: Use Of Rituximab In Ttpmentioning
confidence: 99%
“…4,5 In such refractory/relapsing TTP patients, further immunosuppressive therapy may be required, such as Ciclosporin, cyclophosphamide, or vincristine. Increasingly, rituximab is being reported for the treatment of acute acquired idiopathic TTP, [6][7][8] but only in small case series and anecdotal reports. We present the results of the first phase 2 trial of the use of rituximab, in conjunction with standard therapy (PEX and steroids) within 3 days of admission for acute TTP.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma exchange (PE) has been used to treat TTP/HUS, but the response rate is generally below 50% and the median mortality rate is as high as 79% in the BMT population. 1 Rituximab, an anti-CD20 antibody, has been used to treat recurrent TTP, [2][3][4][5] but there are no reports of its use in TMA associated with BMT (BMT-TMA) and only one report of its use in HUS. 6 We report a patient who developed life-threatening HUS 7 days after undergoing allogeneic BMT (allo-BMT) for acute lymphoblastic leukemia (ALL).…”
mentioning
confidence: 99%
“…[9][10][11] There are numerous reports on the successful use of rituximab in recurrent idiopathic TTP. [2][3][4] De novo TTP is attributed to unusually large von Willebrand factor multimers (ul-vWF) that lead to platelet clumping and microvascular thrombosis. Ul-vWF are normally cleaved into smaller protein units by a metalloprotease called von Willebrand factor-cleaving protease (ADAMTS13).…”
mentioning
confidence: 99%